MEDiastinal Irradiation and CArdio-Toxic Effects (MEDICATE): Exploring the Relationship between Cardiac Irradiation and High Sensitivity Troponins. Issue 7 (July 2019) - Donovan, E.K.; Dhesy-Thind, S.; Swaminath, A.; Leong, D.; Pond, G.; Voruganti, S.; Sussman, J.; Wright, J.R.; Okawara, G.; Kavsak, P.; Dokainish, H.; Fraser, G.; et al.
Abstract: Aims: Radiation-induced heart disease is a late effect of cardiac irradiation and has been shown in patients with lymphoma and thoracic cancers. There is no established measurement tool to detect acute cardiac damage. However, high sensitivity troponin I and T (HsTnI and HsTnT) and echocardiograms have shown promise in some studies. A pilot trial was conducted to characterise whether these instruments may detect subclinical radiotherapy-induced cardiac damage. Materials and methods: Eligible patients received high cardiac doses defined by either at least 30 Gy to 5% of cardiac volume or a mean dose of 4 Gy. HsTnI and HsTnT were measured before radiotherapy and after 2 and 4 weeks of radiotherapy; three-dimensional echocardiograms were completed before and 1 year after radiotherapy. Results: Of 19 patients, the median 'mean left ventricular dose' was 3.1 Gy and the 'mean cardiac dose' was 8.6 Gy. Significant positive associations between HsTnI and HsTnT were observed at all time points, but there was no significant association with cardiac dose. The mean left ventricular dose and the maximum left ventricular dose were, however, associated with a decrease in ejection fraction ( P  = 0.054, 0.043) as well as an increase in left ventricular strain ( P  = 0.058). Conclusion: This study suggests that HsTnI and HsTnT are intimately related, but detection of acute cardiac damage was not shown, potentially due to limitations of these markers or low radiotherapy doses using conformal techniques. Our results also suggest subacute damage at 1 year may depend on the dose to the left ventricle. Further studies are needed, as identification of early damage could facilitate the ability to closely monitor and intervene in patients at risk for radiation-induced heart disease. Highlights: Instruments to identify early RT-induced cardiac damage have not been established. High-sensitivity troponins have shown variable utility and are not well characterized. 3D echocardiograms may detect early change in ejection fraction and strain rate. Relationship between magnitude of subclinical damage and high cardiac doses is unknown.